Implementation of an EDP-Based STEM Project to Develop Students’ Problem-Solving Skills in Light and Heat Energy Concepts - Rifqah Humairah Amir; Tunjungsari Sekaringtyas; Mahmud Yunus (Postgraduate, University of Mataram, 2026)
Elementary science learning requires contextual activities that enable students to apply scientific concepts when addressing real-life problems. However, in-depth qualitative evidence explaining how each Engineering Design Process-based STEM (EDP-STEM) stage supports elementary students’ problem-solving skills remains limited, particularly in light and heat energy learning. This study aimed to describe EDP-STEM implementation through a solar oven project and analyze how its stages supported fifth-grade students’ problem-solving processes. Its novelty lies in mapping five EDP-STEM stages to four problem-solving indicators using multiple qualitative data sources. A qualitative case study was conducted with 26 students in four groups during eight learning sessions. Data were collected through observations, interviews, student worksheets, reflective journals, field notes, rubrics, photographs, and videos. The data were organized, coded, categorized, compared, and interpreted, while credibility was supported through source and method triangulation. Students identified insufficient heat, unstable reflectors, thick plastic covers, and uneven sunlight distribution, then proposed corresponding design modifications. Project scores ranged from 88 to 96; three groups received an A grade and one received a B grade. The clearest evidence concerned problem identification and consideration of possible solutions. Overall, the four indicators emerged through interconnected cycles of designing, testing, evaluating, reflecting, and revising.